Dengue virus serotype 4 in a highly susceptible population in Southeast Brazil - Frederico F. Amâncio; Marcela L. Ferraz; Maria Cristina de M. Almeida; José Eduardo M. Pessanha; Felipe C.M. Iani; Gabriela L. Fraga; José Roberto Lambertucci; Mariângela Carneiro (Elsevier, 2014)
Summary: In Minas Gerais, Brazil, almost 500,000 dengue fever cases were reported to the State Surveillance System between November 2012 and July 2013. An analysis of the laboratory-confirmed cases revealed a higher age-specific incidence in adults and a higher case fatality rate in people aged ≥50. Dengue virus serotypes 1 and 4 (the latter of which is an emerging serotype in Brazil) were responsible for the outbreak. Keywords: Dengue, Brazil, Outbreak, Dengue serotype 4, Epidemiology